Gen Z Tourism Employees’ Adaptive Performance During a Major Cultural Shift: The Impact of Leadership and Employee Voice Behavior - Kleanthis K. Katsaros (Behavioral Sciences)
Based on social exchange theory and the norm of reciprocity, the current study proposes a mediation model to assess the role of employee voice behavior (promotive and prohibitive) on the relationship between leadership (i.e., transformational, inclusive, and adaptive) and Gen Z employees’ adaptive performance (AP). Research data were obtained from 195 Gen Z employees and their supervisors from a group of luxury hotels located in Greece that had experienced a major cultural shift. The research model was examined using the structural equation modeling technique (SEM) with maximum likelihood estimation using the analysis of moment structures program (AMOS version 24). The research findings indicate that (a) all three leadership approaches positively influence Gen Z employees’ AP, (b) promotive voice behavior mediates the relationship between all leadership approaches and Gen Z employees’ AP, and (c) prohibitive voice behavior mediates the relationship between inclusive leadership and Gen Z employees’ AP. The results suggest that by implementing human-centered practices and procedures to positively influence Gen Z employees’ voice behavior, tourism leaders/managers can increase their AP.